2023
DOI: 10.1002/jmv.28993
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter virome analysis of blood, feces, and saliva in myalgic encephalomyelitis/chronic fatigue syndrome

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is estimated to affect 0.4%–2.5% of the global population. Most cases are unexplained; however, some patients describe an antecedent viral infection or response to antiviral medications. We report here a multicenter study for the presence of viral nucleic acid in blood, feces, and saliva of patients with ME/CFS using polymerase chain reaction and high‐throughput sequencing. We found no consistent group‐specific differences other than a lower prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…This fungal-related coinfection has been linked to elevated mortality rates in COVID-19 patients, with approximately 54.6% case fatality rate associated with secondary fungal infections [51] . Evidence of active viral and fungal infections in individuals with ME/CFS who experience prolonged and unexplained symptoms was also indicated by previous studies [52] , although no significant ME/CFS-specific differences were identified in our recent research utilizing unbiased high-throughput sequencing, capture sequencing, and both multiplex and targeted PCR assays [53] .…”
Section: Microbiome Dysbiosissupporting
confidence: 78%
“…This fungal-related coinfection has been linked to elevated mortality rates in COVID-19 patients, with approximately 54.6% case fatality rate associated with secondary fungal infections [51] . Evidence of active viral and fungal infections in individuals with ME/CFS who experience prolonged and unexplained symptoms was also indicated by previous studies [52] , although no significant ME/CFS-specific differences were identified in our recent research utilizing unbiased high-throughput sequencing, capture sequencing, and both multiplex and targeted PCR assays [53] .…”
Section: Microbiome Dysbiosissupporting
confidence: 78%
“…Additionally, the authors also found differences in metabolomic pathways, involving unsaturated fatty acid synthesis, atrazine degradation, vitamin B6 synthesis and pyrimidine ribonucleoside degradation. As the intestinal microbiome consists of bacterial and viral species, and give the fact, that ME/CFS is, despite a high number of unexplained cases, frequently reported as post-viral sequela such as after SARS-CoV-2 ( 72 ), another study focused on viral taxa in feces, blood and saliva, however, the authors did not observe any differences between ME/CFS patients and controls ( 73 ).…”
Section: Microbiota-gut-brain Axis In Me/cfsmentioning
confidence: 99%